If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 47 = 6z + -16 Reorder the terms: 47 + 2z = 6z + -16 Reorder the terms: 47 + 2z = -16 + 6z Solving 47 + 2z = -16 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 47 + 2z + -6z = -16 + 6z + -6z Combine like terms: 2z + -6z = -4z 47 + -4z = -16 + 6z + -6z Combine like terms: 6z + -6z = 0 47 + -4z = -16 + 0 47 + -4z = -16 Add '-47' to each side of the equation. 47 + -47 + -4z = -16 + -47 Combine like terms: 47 + -47 = 0 0 + -4z = -16 + -47 -4z = -16 + -47 Combine like terms: -16 + -47 = -63 -4z = -63 Divide each side by '-4'. z = 15.75 Simplifying z = 15.75
| 2(12y-11)=-4(1-6y) | | -(x-8)+4=2(12)+x | | 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 |